Balanced Scorecard Analysis as A Performance Measurement Tool PT Japfa Makassar - Fausiah, Rafika; Samsuri, Samsuri; Wijaya, Hasrul; Ramli, Muh. (Perpustakaan dan Penerbitan Unismuh Makassar, 2023)
Performance appraisal plays an important role in the business world, because with the performance appraisal it can detect weaknesses or deficiencies that still exist in the company, for further improvements in the future. This study aims to determine how the implementation of performance measurement of PT Japfa Comfeed Indonesia using the concept of the Balanced Scorecard. The research was conducted at PT. Japfa Makassar which is located in the industrial area of Makassar. The population of this study is all company information related to measuring performance with the Balanced Scorecard approach. In this study, to determine the financial performance of the population there is a financial report, in terms of customers the population is all customers of PT. Japfa Makassar, to determine the performance from the perspective of growth and learning the population is all employees of PT. Japfa Makassar, for measuring performance from the perspective of the internal business population, there are operating activities of PT. Japfa Makassar. The number of samples taken respectively is 50 respondents for employees and 50 respondents for customers. The results show that performance appraisal using the balanced scorecard method can determine the company's success not only from an internal perspective, in this case, a financial perspective, but also from all aspects, be it financial, process, growth, and customer aspects